Modelo Prolab: Reporte recojo recompensa, un sistema integrado de recojo, comercialización de materiales reciclables y producción de compost - Blandón Hernández, Ana Patricia (2024)
The "Reporte Recojo Recompensa" project addresses the issue of inadequate solid waste management in Chiclayo, Peru, focusing on an integrated system that properly manages waste, transforms organic waste into compost, and promotes recycling. This approach not only improves public health and reduces pollution but also generates economic opportunities by valuing a higher volume of waste, while simultaneously fostering education in recycling practices. The project aligns with the United Nations' Sustainable Development Goals (SDGs) 12 and 13, specifically in efficient resource management and climate action. The solution's second most important process involves converting organic waste into compost through a controlled decomposition and maturation process, resulting in high- quality compost. This compost will be marketed through direct sales to farmers, promoting its use as a natural fertilizer that improves soil quality and restores its mineral properties. The venture has demonstrated significant financial impact, a highly valued aspect for potential business participants. It has been concluded to be financially viable, with a Net Present Value (NPV) of $728,603, an Internal Rate of Return (IRR) of 120%, and a payback period of two years, highlighting its profitability and long-term sustainability. Socially, the impact is significant: a considerable reduction in waste generation and improved resource management are expected. Additionally, environmental sustainability education and awareness promoted through the mobile application will contribute to greater community participation in waste segregation activities and reporting events that lead to pollution.